2014
DOI: 10.1242/jeb.089490
|View full text |Cite
|
Sign up to set email alerts
|

Surviving in a frozen desert: environmental stress physiology of terrestrial Antarctic arthropods

Abstract: Abiotic stress is one of the primary constraints limiting the range and success of arthropods, and nowhere is this more apparent than Antarctica. Antarctic arthropods have evolved a suite of adaptations to cope with extremes in temperature and water availability. Here, we review the current state of knowledge regarding the environmental physiology of terrestrial arthropods in Antarctica. To survive low temperatures, mites and Collembola are freeze-intolerant and rely on deep supercooling, in some cases superco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 84 publications
0
56
0
Order By: Relevance
“…Belgica, a Belgian exploratory ship that plied the waters off the Antarctica Peninsula at the end of the 19 th century 4 . In its patchy island habitat along the Antarctic Peninsula, B. antarctica is subjected to a range of environmental onslaughts including temperature extremes, periodic desiccation, exposure to both fresh water ice melt and high salinity sea water, intense ultra-violet exposure, high nitrogen generated from penguin rookeries and elephant seal wallows, and high winds 5, 6, 7 . The adults, like those of many other species living on wind-swept islands, are apterous (wingless).…”
Section: Introductionmentioning
confidence: 99%
“…Belgica, a Belgian exploratory ship that plied the waters off the Antarctica Peninsula at the end of the 19 th century 4 . In its patchy island habitat along the Antarctic Peninsula, B. antarctica is subjected to a range of environmental onslaughts including temperature extremes, periodic desiccation, exposure to both fresh water ice melt and high salinity sea water, intense ultra-violet exposure, high nitrogen generated from penguin rookeries and elephant seal wallows, and high winds 5, 6, 7 . The adults, like those of many other species living on wind-swept islands, are apterous (wingless).…”
Section: Introductionmentioning
confidence: 99%
“…Both cold and desiccation stress result in decreased hemolymph volume and increased hemolymph osmolarity (4), so it is reasonable to expect mechanistic overlap between these stresses. Indeed, similar molecular mechanisms, including calcium signaling pathways, appear to modulate cold and desiccation responses (5,6). Several studies have shown that freezetolerant insects can improve their cold tolerance in response to a mild desiccation stress (7)(8)(9), and artificial selection for desiccation tolerance in Drosophila melanogaster impacts the ability to recover from chill coma (10).…”
mentioning
confidence: 99%
“…Seasonal and stress‐induced accumulation of low molecular mass cryoprotectants is a characteristic of cold hardy arthropods, both freeze tolerant and freeze avoidant (Teets & Denlinger, ). In both species examined in the present study, glucose and sucrose are found to be the most abundant metabolites in all samples, both control and treated, suggesting a key role as cryoprotectants.…”
Section: Discussionmentioning
confidence: 99%